2006
DOI: 10.1093/jxb/erl174
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium rhizotoxicity in maize grown in solutions with Al3+ or Al(OH)4- as predominant solution Al species

Abstract: The rhizotoxicity of aluminium at low-pH with Al(3+) and at high pH with Al(OH)-(4) as the main Al species was studied. Aluminium reduced root growth to similar levels at pH 8.0 and pH 4.3, although the mononuclear Al concentration at pH 8.0 was three times lower than at pH 4.3. Al contents of root apices were much higher at pH 8 than at pH 4.3. Callose was induced only marginally at pH 8 and the formation was confined to the epidermis, whereas it proceeded through the cortex with time at pH 4.3. Well-document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Stass et al (2006) found that Al mainly existed as biologically toxic Al 3+ at rhizosphere pH < 4.3. Contents of active Al 3+ were decreased when the rhizosphere pH was increased from 4.0 to 5.0 (Zhu et al 2005).…”
Section: Resultsmentioning
confidence: 96%
“…Stass et al (2006) found that Al mainly existed as biologically toxic Al 3+ at rhizosphere pH < 4.3. Contents of active Al 3+ were decreased when the rhizosphere pH was increased from 4.0 to 5.0 (Zhu et al 2005).…”
Section: Resultsmentioning
confidence: 96%
“…It functions as a physical barrier against many stress factors, which may threaten to penetrate the protoplast, e.g., biotic threats such as fungal pathogens (Bolwell et al 2002), or abiotic threats including wounding (Jacobs et al 2003) and TM stress (e.g., Hématy et al 2009). Callose appearance under TM stress has been observed in the response of a range of plant species, e.g., in response to Pb in Lemna minor (Samardakiewicz et al 1996) and F. hygrometrica protonemata (Krzesłowska et al 2009a), and to Al in Triticum aestivum (Sivaguru et al 2000), A. thaliana (de Cnodder et al 2005) and Zea mays (Stass et al 2006). In plants exposed to Al, it has been shown that callose deposition was inducted by the appearance of ROS in the CW and alteration of calcium homeostasis, mainly its increase within protoplast caused by the metal (Sivaguru et al 2000;Jones et al 2006).…”
Section: Detection Of Tms In Plant Cell Wallmentioning
confidence: 99%
“…It was recognized that significant accumulation of Al in the cell walls may alter their structural and mechanical properties, and thus affect the root growth (Wang et al 2004). The Al binding to sensitive binding sites in the apoplast of the epidermis and the outer cortex of roots has been shown to inhibit root growth in maize (Stass et al 2006). The Al binding to these negatively charged sites can lead to displacement of Ca 2+ , fundamental for cell-wall stability (Rincon & Gonzales 1992;Tabuchi & Matsumoto 2001).…”
Section: Aluminum Toxicity In Maize Rootsmentioning
confidence: 99%